Where Is Herod's Tomb at Herodium? - Magness, Jodi (Bulletin of ASOR, 2001)
Although scholars accept Josephus's testimony that Herod the Great was buried at Herodium, his tomb has never been found. The absence of fine wares dating to the first century C. E. indicates that Upper Herodium ceased to function as a palace after Herod's death and supports the view that he was buried inside the mountain.